Microscopic Evaluation of Leaf of Balanites Aegyptiaca (L.) Delile: A Review Article - Rathore, Bhawani Singh; Kotecha, Mita; Chaudhary, Krutika; Manjula (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: Leaves of Balanites aegyptiaca (L.) Delile are commonly used for diabetes. Literature survey revealed that not much work has been done on this plant, especially on leaves. So detailed microscopical study was done for its identification. Methods: Transverse section and powder microscopy was carried out on leaves of Balanitesaegyptiaca (L.) Delile. Result: Microscopical study showed dorsiventaral midrib and smooth, even and thick lamina. The lamina was isolateral and 350 µm thick. The marginal part of the lamina was bluntly conical measuring 200 µm thick. Calcium oxalate crystals were abundant in the mesophyll tissue. The crystals were druses and rosette types. The veins formed well defined vein-islets of polygonal outline. The vein terminations were well developed and thick, short and straight. At the end of the vein termination occurred a cluster of squarish, thick walled wide sclereids. The leaf was amphistomatic, However, the stomata on the abaxial side were more in frequency than on the adaxial side. The abaxial epidermal cells were small, polygonal and fairly thick walled. The anticlinal walls were straight. The trichomes were unicellular, unbranched and thick walled. Crystal bodies were wide spread in the powder. The crystals were exclusively druses, which were spherical bodies comprising many pointed triangular small crystal units. Analysis and Discussion: The present research provided useful information in regard to its correct identity, evaluation and helped to differentiate from the closely related other species of Balanites aegyptiaca (L.) Delile. Hence, it furnished the data for future standardization of the drug.